Digital Marketing- A Study on Internet Advertising, SMS Advertising and Blog with emphasis on Alcohol Brands in Malaysia - Chan, Wai Fong (2007)
The dynamic evolution of technologies offers boundless opportunities for marketing communication, especially for alcohol brands in Malaysia which are in the “semi-dark market” environment and are restricted from mass advertising, the introduction of digital marketing certainly gave rise to a new ray of hope. The aim of this study is to examine the consumers’ response toward the three marketing communication choices i.e. Internet ad, SMS ad and blog and recommend the method to capitalise on these tools effectively. Among many methods for examining the effectiveness of digital marketing, a model of successful digital marketing advertising was adapted from Scharl et al (2005). A questionnaire was developed and to which a total of 179 respondents from Klang Valley participated in the survey. A statistical software application named SPSS version 15 was used to analyse the data collected. An interview was also conducted with a popular blogger in Malaysia. The result of the empirical study showed that each of the three digital marketing communication tools has its own individual strengths and weaknesses. Having combined the literature reviews and the research result, this study presents the factors that contribute to the success of a marketing campaign. In conclusion, each individual digital marketing choice should not be a “stand alone” tool. To maximise their capabilities, all three choices are to be combined and complement each other. To ensure an effective and successful marketing campaign, a strategy on integration of both traditional and digital marketing communication choices is recommended.